Cigarette smoking impairs the diaphragm muscle structure of patients without respiratory pathologies: An autopsy study - Nucci, Ricardo Aparecido Baptista (2019)
Background/Aims: Smoking is a major risk factor for several cardiovascular and pulmonary diseases, and it has also been associated with the loss of skeletal muscle mass and strength leading to sarcopenia. The aim of this is study is to analyze the effects of cigarette smoking on the diaphragm muscle histopathology of postmortem samples from patients without respiratory diseases. Methods: Diaphragm samples were stained with hematoxylin and eosin for histopathological analysis. Picrosirius stain was used to highlight the collagen fibers. Results: Cigarette smokers had an increase of histopathological alterations as abnormal cytoplasm, abnormal fiber size and shape, and central nucleus. Additionally, smokers had an increase of collagen fibers on diaphragm muscle. Conclusion: Smoking may influence in a negatively fashion the diaphragm musculature.